Acquired Initiating Mutations in Early Hematopoietic Cells of CLL Patients - Damm, Frederik; Mylonas, Elena; Cosson, Adrien; Yoshida, Kenichi; Della Valle, Véronique; Mouly, Enguerran; Diop, M'boyba; Scourzic, Laurianne; Shiraishi, Yuichi; Chiba, Kenichi; Tanaka, Hiroko; Miyano, Satoru; et al. (Cancer discovery, 2014)
Appropriate cancer care requires a thorough understanding of the natural history of the disease, including the cell of origin, the pattern of clonal evolution, and the functional consequences of the mutations. Using deep sequencing of flow-sorted cell populations from patients with chronic lymphocytic leukemia (CLL), we established the presence of acquired mutations in multipotent hematopoietic progenitors. Mutations affected known lymphoid oncogenes, including BRAF, NOTCH1, and SF3B1. NFKBIE and EGR2 mutations were observed at unexpectedly high frequencies, 10.7% and 8.3% of 168 advanced-stage patients, respectively. EGR2 mutations were associated with a shorter time to treatment and poor overall survival. Analyses of BRAF and EGR2 mutations suggest that they result in deregulation of B-cell receptor (BCR) intracellular signaling. Our data propose disruption of hematopoietic and early B-cell differentiation through the deregulation of pre-BCR signaling as a phenotypic outcome of CLL mutations and show that CLL develops from a pre-leukemic phase. Significance: The origin and pathogenic mechanisms of CLL are not fully understood. The current work indicates that CLL develops from pre-leukemic multipotent hematopoietic progenitors carrying somatic mutations. It advocates for abnormalities in early B-cell differentiation as a phenotypic convergence of the diverse acquired mutations observed in CLL. Cancer Discov; 4(9); 1088–1101. ©2014 AACR. See related commentary by Jiang and Elemento, p. 995 This article is highlighted in the In This Issue feature, p. 973